Gel-Based Autologous Chondrocyte Implantation in a Patient with Noncontained Osteochondral Knee Defect at 9-Year Follow-Up - Ujjval Deliwala; Sumit Jain Sethia (Case Reports in Orthopedics)
Osteochondritis dissecans (OCD) is a disorder of the subchondral bone affecting the adjacent articular cartilage that may lead to cartilage and bone fragment detachment. It commonly occurs in the knee joint, elbow, wrist, and ankle. Although several surgical concepts have been described to treat OCD (fragment fixation, microfracture, autologous chondrocyte implantation (ACI), and mosaicplasty), no gold standard treatment has been accepted for managing OCD. Multiple factors like age, stability of defect, and defect size should be considered while selecting a specific treatment for OCD. Here, we discuss the case of an 18-year-old patient with horizontal and noncontained OCD. The MRI and CT scan evaluations of condylar notch view showed a defect (23 mm×19 mm×8 mm) with ICRS grade IV lateral femoral condyle OCD that was successfully managed by gel-based ACI. After 9 years of ACI, the patient was asymptomatic with full range of motions at the knees. Improvement in visual analog scale score, International Knee Documentation Committee score, and Magnetic Resonance Observation of Cartilage Repair Tissue score was also seen at 9 years post-ACI. No further surgical interventions were needed post-ACI.